Interpretação de textos literários e não literários e produção textual de alunos de ensino fundamental, numa perspectiva complexa e transdisciplinar - Santos, Clarice dos (2021)
This work deals with the arguments and the elaboration of a paradidactic material for Portuguese Language and Literature teachers who work with the final years of Elementary School, in order to instrumentalize them with a material composed by the transdisciplinary and complex perspectives, involving several disciplines, such as: History, Art, Pedagogy, Psychology, Geography, Psychoanalysis, Music and Linguistics, in order to assist students in reading and understanding texts and to carry out their own textual productions, becoming thus, competent, critical and autonomous readers and authors. The execution of this procedure was based on the theories of several scholars, among them, Bakhtin, (1999, 2011) related to the textual genre, the text, Benveniste (1989), Marcuschi (2008) regarding the understanding of reading and text production , Edgar Morin (2007), regarding the theory of transdisciplinarity and complexity, Nicolescu (1999, 2008) on the theory of transdisciplinarity, Morais (2015) on his contributions also regarding transdisciplinarity, Paulo Freire (2007, 2012) through his extensive experience in education, Gadotti (2010) with regard to teaching work, all linked to the guidelines of the PCN (1998) and the BNCC (2018). We also included parts of the theories of scholars from other sciences, pertinent to this study, such as: Vygotsky (1991) on his studies related to language learning and acquisition, Freud (1927, 1976) Jung (2000) regarding his studies on Psychoanalysis and language, Lacan (1953, 1981) and his contributions on the process of installing language in human beings. The importance of this work lies in the collaboration with the work of the Portuguese Language and Literature teacher, so that they have a paradidical material that has, as its main characteristic, activities that include texts related to various disciplines. This is the main objective of this work.